2004
DOI: 10.1076/chin.9.4.237.23514
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Girls With ADHD and Comparison Girls On the Rey-Osterrieth Complex Figure: Evidence for Executive Processing Deficits

Abstract: In spite of a multitude of scoring approaches, the ability of the Rey-Osterrieth Complex Figure (ROCF) to measure executive functions versus grapho-motor skill is still open to question. To clarify this issue, we examined the performance of an ethnically and socioeconomically diverse sample of preadolescent girls (ADHD-Combined, n = 93; ADHD-Inattentive, n = 47; and comparison girls, n = 88) on the ROCF, scoring both immediate copy and delayed recall performance. Girls with ADHD performed the task following a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 0 publications
0
45
2
1
Order By: Relevance
“…The priority was placed on well-established and well-validated neuropsychological tests, most of which were parallel forms to those used at baseline (see Hinshaw et al, 2002) Figure (ROCF), which at baseline had been our most sensitive neuropsychological/executive test for discriminating the ADHD from the comparison sample (Hinshaw, 2002;Sami et al, 2003). The ROCF is used to evaluate planning, perceptual organization, and graphomotor abilities (Lezak, 1983;Spreen & Strauss, 1998).…”
Section: Cognitive and Neuropsychological Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The priority was placed on well-established and well-validated neuropsychological tests, most of which were parallel forms to those used at baseline (see Hinshaw et al, 2002) Figure (ROCF), which at baseline had been our most sensitive neuropsychological/executive test for discriminating the ADHD from the comparison sample (Hinshaw, 2002;Sami et al, 2003). The ROCF is used to evaluate planning, perceptual organization, and graphomotor abilities (Lezak, 1983;Spreen & Strauss, 1998).…”
Section: Cognitive and Neuropsychological Measuresmentioning
confidence: 99%
“…The current scoring system was parallel to the one used at baseline, which had been developed from our modifications of the procedures of Bernstein and Waber (1996), as described in Sami et al (2003). Drawings were scored by a group of three extensively trained, independent raters who were unaware of diagnostic status.…”
Section: Cognitive and Neuropsychological Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the extant pediatric literature, the ROCF has been utilized as a measure of visuospatial perception, learning and memory (Baron, 2000) in research with several populations including typically developing youth (Beebe, Ris, Brown, & Dietrich, 2004), epilepsy (Hernandez et al, 2003), phenylketonuria (Antshel & Waisbren, 2003), preterm children (Waber & McCormick, 1995), learning disabilities (Kirkwood et al, 2001) and ADHD (Sami, Carte, Hinshaw, & Zupan, 2003;Seidman et al, 1995). All of these studies found the ROCF to be a sensitive measure to the cognitive difficulties of the identified clinical group.…”
Section: Rey-osterrieth Complex Figurementioning
confidence: 99%